2008
DOI: 10.1007/s10549-008-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of cancer cells by autologous T cells in breast cancer pleural effusates treated with anti-EpCAM BiTE antibody MT110

Abstract: In the present study, the efficacy of a new drug, i.e. the bispecific single-chain antibody MT110 targeting the epithelial antigen EpCAM and the T-cell antigen CD3 was tested ex vivo in malignant pleural effusions (MPEs). EpCAM ? epithelial cells were found in 78% of the MPEs (n = 18). Ex vivo treatment of seven MPEs resulted in a dose-dependent specific lysis of 37 ± 27% (±SD) EpCAM ? cells with 10 ng/ml (P = 0.03) and 57 ± 29.5% EpCAM ? cells with 1,000 ng/ml MT110 (P = 0.016) after 72 h. As a prerequisite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…The influence of 4-1BB blockade on direct and Rituximabinduced lysis of CLL cells by autologous NK cells was determined by FACS as previously described [43]. In brief, PBMCs of CLL patients were incubated with or without Rituximab in the presence or absence of blocking 4-1BB antibodies or isotype control.…”
Section: Facs-based Analysis Of Cll Cell Lysismentioning
confidence: 99%
“…The influence of 4-1BB blockade on direct and Rituximabinduced lysis of CLL cells by autologous NK cells was determined by FACS as previously described [43]. In brief, PBMCs of CLL patients were incubated with or without Rituximab in the presence or absence of blocking 4-1BB antibodies or isotype control.…”
Section: Facs-based Analysis Of Cll Cell Lysismentioning
confidence: 99%
“…Clinical studies are ongoing in adult and pediatric patients with relapsed/refractory B-precursor ALL, adults with persistent minimal residual disease B-precursor ALL, and adults with relapsed diffuse large B cell lymphoma (DLBCL), (ClinicalTrials.gov identifiers NCT01471782, NCT01207388, NCT01466179, and NCT01741792). Solitomab targets EpCAM on both epithelial carcinomas as well as tumor-initiating cells, [50][51][52] and has entered a Phase I trial in patients with solid tumors that express EpCAM (ClinicalTrials.gov identifier NCT00635596). AMG 212 is being tested in a Phase I trial in patients with castration-resistant prostate adenocarcinoma (ClinicalTrials.gov identifier NCT01723475).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models have shown high levels of activity of BiTE antibodies targeted against EphA2 and CD19 (Dreier et al, 2003;Schlereth et al, 2006;Brischwein et al, 2006;Offner et al, 2006;Hammond et al, 2007). Witthauer et al (2008) reported that a BiTE targeting EpCAM could lead to T-cell-mediated killing of breast cancer cells in pleural effusions. Recently, Bargou et al (2008) reported clinical activity and a safety profile suitable for continued development of the BiTE antibody blinatumomab (also called MT103/MEDI-538) with dual specificity for CD19 and CD3 in a study of non-Hodgkin's B-cell lymphoma patients who had experienced relapse after standard therapies.…”
mentioning
confidence: 99%